Using Eye-Tracking in Education—A Review Study - Vlastimil Chytry; Nikola Mundokova; Milan Kubiatko (Education Sciences)
Visual perception is a complex psychological operation that is used to understand our environment. Its measurement gradually penetrates various areas of human life as well as the educational process. The presented study has a theoretical–analytical character; its aim was to identify the nature of publications that are devoted to the issue of eye-tracking focused on the educational process. The selection of the analyzed articles was carried out in the Web of Science database in January 2021, and all peer-reviewed articles (marked articles) that were in the Education category were included in the Educational Research database. Those texts were further analyzed with the use of the generally recognized PRISMA guidelines. The number of studies that are focused on eye-tracking had an upward trend, studies from Europe were the most often represented, the authors focused on reading comprehension, and the most common sample were university students. Implications for practice and suggestions for further research can be found in the conclusion.